The future of energy use - O'Keefe, Philip; O'Brien, Geoff; Pearsall, Nicola (Earthscan, 2010)
Following the success of its predecessor, this second edition of The Future of Energy Use provides essential analysis of the use of different forms of energy and their environmental and social impacts. It examines conventional, nuclear and renewable sources and technologies, using relevant case studies and providing a vital link between technology and related policy issues. The new edition has been comprehensively developed and updated, including new text, diagrams and tables, with entire new sections that reflect the significant changes that have occurred since the first edition